Influence of price changes on the users at the strategic pricing on generic products - V.L. Korinev; V.V. Kirik (Marketing i Menedžment Innovacij, 2010)
At the generic commodities sales the market value of producer depends on the reaction of buyers on the price changes. The analyze shows that under certain circumstances costumers can behave to the price as the index of quality. So customers can be less sensible to the price level, than to consumer descriptions of generic products. If the level of generic products price is associated with the level of its quality, the less than they are sensible to the change of its level. In the process of the strategic pricing producers, which takes into account maximum of high or low prices, can define the degree of costumers sensitiveness to the price.